Usage of Classroom Technology and the Technological Pedagogical Content Knowledge (TPACK) of Mathematics Teachers - Junymer Callo Plantado (Southeast Asian Mathematics Education Journal, 2023)
Technological Pedagogical Content Knowledge (TPACK) is a theoretical framework in technology integration that is highly regarded in today's digital era. Using a descriptive research design, this study investigated 81 secondary mathematics teachers' use of available classroom technology and level of competence in the eight TPACK domains. The findings revealed that classroom technology was rarely employed. This was due to a combination of external and internal factors. While along the TPACK domains, the teachers obtained the highest level of competence in CK (M = 4.29, SD = .59) and lowest in TK (M = 3.69, SD = .70). One-way ANOVA uncovered that there was a highly significant difference in the level of competence along with TPACK domains. Furthermore, correlation and multiple regression analysis unveiled that the level of usage of classroom technology was discovered to be highly significant and served as the best predictor of TK (F(6, 74) = 6.17, p<.001), TPK (F(6, 74) = 6.39, p<.001), TCK (F(6, 74) = 4.30, p<.001), and TPACK (F(6, 74) = 2.65, p =.022). Implications of the findings and recommendations are discussed.